Preservation and the restoration of mental health from the Qur'anic perspective - Abdul Razak, Abdul Latif (2015)
The Qur’an is the comprehensive guidance, not only for Muslims, but also for the whole mankind. It is revealed for the benefits of the people in every corner and aspect of their lives. One of the aspects is in the preservation and restoration of mental health. This paper aims at analyzing the significance of the Qur’an and Sunnah, i.e. their teachings in preserving mental health as well as in restoring its healthy state. It is an attempt to explore the richness of Qur’an in offering such an important resource in the area, so that it can be benefitted by the people at large. This study also will benefit from the works of early Muslim scholars in the area of counseling and psychotherapy on the assumption that their writings are inspired by their understanding of the two main sources of Islam. It is hoped that this paper will enlighten us on the importance of revelation in the preservation and the restoration of mental health.